Taking a Cross-Faculty Stand Against Racism and Inequality: What Are Enabling and Inhibiting Factors Influencing the Placement Experiences of Black, Asian, Ethnic Minoritised Students in the Schools of Social Work, Education, and Health Sciences? - Carlene Cornish; Stephanie T. Jong; Isabella Albarran; Swati Kale; Sarah Brownsword; Cat Playfair; Sophie Vauzour; Tina Odu; Godfrey Lusigi; Virginia Shikuku (Genealogy)
Many Black, Asian, and ethnic minoritised students on university courses leading to professional qualifications face racism on placement. Our own institutional review at one UK university highlighted differential placement outcomes for students in the Schools of Social Work, Education, and Health Sciences. To investigate, a qualitative study was conducted between April to October 2024, using focus groups and interviews with 20 students and 19 staff (lecturers and placement supervisors from the NHS, County Council, and schools). Researchers used NVivo to support the thematic analysis of the qualitative data. Key findings identified various enabling factors, including the significance of supervisory placement support and the quality of placement environment. However, our data further confirmed several inhibiting factors, including power dynamics, systemic failures, and broken trust, contributing to racialised and oppressive placement conditions. We recommend that the university and placement providers have a dedicated system for reporting race-specific incidents to a dedicated person/team who are trained and accountable for tackling and preventing racists incidents on placements.